The formation of a teacher’s informational culture: theoretical aspect (Pedagogy of Higher and Secondary Education, 2013)
Stykalova T. G. The formation of a teacher’s informational culture: theoretical aspect.The article examines the influence of the informational society on the formation of a teacher’s informational culture. The structure and level of informational culture of the teacher and the necessity of using information and communication technologies on the classes to ensure the effectiveness of the learning process are examined.
Keywords: information; informatization; teacher’s informational culture; information and communication technologies